Review of recent advances in managing periocular skin malignancies - Trotier, Daniel C.; Huang, Leslie; van Landingham, Suzanne W.; Burr, Adam R.; Ma, Vincent T. (Frontiers in Oncology, 2024)
Management of cutaneous malignancies can be particularly challenging when they are located in the periocular region. The standard of care for localized disease is complete surgical excision, but this may not be possible without significant disruption to visual structures and facial appearance. Definitive radiation may be an option for some patients who cannot or do not wish to undergo surgery. Advances in systemic treatment options for locally advanced and metastatic skin cancers in the past 10 years have prompted investigation into neoadjuvant treatment of periocular cancers. The use of chemotherapy, immune checkpoint inhibitors, and targeted therapies have all been reported with varying degrees of success. For many patients, targeted therapies or immune checkpoint inhibitors should be considered depending on the cancer type, symptoms, and goals with the input of a multidisciplinary cancer care team. In this article, we systematically review the latest updates in surgical, radiotherapeutic, and medical management of periocular malignancies.